Analysis of factors associated with early menarche in adolescents - Brivian Florentis Yustanta (Science Midwifery, 2023)
The incidence of menarche praecox is 5.2% of adolescents in Indonesia. Indonesia ranks 15th out of 67 countries with a decline in menarche age of up to 0.145 years per decade. The study aimed to analyze factors associated with early menarche (praecox menarche) in adolescents. This type of analytic research with quantitative methods and crosssectional research design. This used primary data, the instruments used microtoise, weight scales, and checklists. The population was 145 adolescents. The sample size was 124 respondents using simple random sampling. The research was tested using the Chi Square test. It was conducted in Kediri on October to December 2022. The research results were found that adolescents who experienced praecox menarche were 41.9%, nutritional status was not obese by 75.2%, exposed to pornography by 65.6%, genetics (early menarche age of mother) by 51.2%, not active in sports by 69.6%. From the results of data analyze it can be concluded that there was no correlation between nutritional status and praecox menarche (P-value 0.100), there was correlation between exposure to pornography and praecox menarche (P-value 0.000), there was correlation between genetics and praecox menarche (P-value 0.002), there was correlation between physical activity (exercise) and praecox menarche (P-value 0.001).